Hydrogen Bonding Regulates the Rigidity of Liposome‐Encapsulated Chlorin Photosensitizers. Issue 6 (20th June 2018) - Vetta, Martina De; González, Leticia; Nogueira, Juan J.
Abstract: Liposomal formulations facilitate the administration of hydrophobic drugs, avoiding precipitation and aggregation phenomena when injected in polar solvents. The integration of the photosensitizer into the liposome may alter the fluidity of the system and, thus, modify the delivery process of the drug. Such a change has been observed for the liposomal formulation of Temoporfin, which is one of the most potent chlorin photosensitizers employed in photodynamic therapy. Here, all‐atom molecular dynamics simulations have been performed to identify the nature of the intermolecular interactions that might be responsible of the different lipids freedom of motion when the drug is introduced in the bilayer. It is found that Temoporfin participates as a hydrogen donor in strong hydrogen‐bonding interactions with the polar groups of the phospholipids. The theoretical analysis suggests that the rigidity of drug/liposome complexes can be modulated by considering the different hydrogen‐bond ability of the photosensitizer and the carrier material. Abstract : Hydrogen tug of war : Hydrogen bonding plays a crucial role in determining the loading capacity and the lipid fluidity of liposomal formulations for chlorin derivatives.